A metaheuristic for a numerical approximation to the mass transfer problem - Avendaño-Garrido, Martha L.; Gabriel-Argüelles, José R.; Quintana-Torres, Ligia; Mezura-Montes, Efrén (International journal of applied mathematics and computer science, 2016)
This work presents an improvement of the approximation scheme for the Monge-Kantorovich (MK) mass transfer problem on compact spaces, which is studied by Gabriel et al. (2010), whose scheme discretizes the MK problem, reduced to solve a sequence of finite transport problems. The improvement presented in this work uses a metaheuristic algorithm inspired by scatter search in order to reduce the dimensionality of each transport problem. The new scheme solves a sequence of linear programming problems similar to the transport ones but with a lower dimension. The proposed metaheuristic is supported by a convergence theorem. Finally, examples with an exact solution are used to illustrate the performance of our proposal.